Thick Mucus in ALS: A Mixed-Method Study on Associated Factors and Its Impact on Quality of Life of Patients and Caregivers - Sarah K. Bublitz; Eva Mie; Maria Wasner; Alexander Hapfelmeier; Jens Geiseler; Stefan Lorenzl; Andrea Sylvia Winkler (Brain Sciences, 2022)
In this explorative mixed-method pilot study, we set out to have a closer look at the largely under-recognized and under-investigated symptom of thick mucus in patients with ALS and its impact on patients and relatives. Thick mucus is a highly distressing symptom for both patients and caregivers. It complicates the use of non-invasive ventilation and is therefore an important prognostic factor of survival. Methods: In our preliminary study, we used a cross-sectional design, including ten ALS patients with thick mucus who were matched to ten ALS patients without thick mucus. Lung function tests and laboratory and sputum analysis were performed and questionnaires administered in order to determine associated factors of thick mucus accumulation. In a qualitative study using semi-structured interviews, we analysed the impact of thick mucus on patients and caregivers. Results: Reduced respiratory parameters as well as a higher degree of bulbar impairment were associated with the presence of thick mucus. Quality of life of patients and caregivers was strongly impaired by thick mucus accumulation. Conclusions: Thick mucus in patients with ALS has a strong impact on quality of life. Reduced cough flow and severely impaired bulbar function appear to be indicative parameters. We suggest that healthcare providers actively explore the presence of thick mucus in their patients and that it becomes included in commonly used screening tools.